Preparation method of quartz fiber reinforced wave-absorbing composite material resistant to high-energy laser irradiation
Through gradient gradient design and surface treatment technology, combined with hot press forming process, the functional filler formula of quartz fiber reinforced composite materials is optimized, which solves the problems of high-energy laser radiation and electromagnetic wave attenuation, and realizes the material's high-energy laser resistance, wide-frequency wave absorption and The mechanical strength compatible design improves the comprehensive protection capability of drone equipment.
Patent Information
- Application Number
- CN202411352412.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
AI Technical Summary
The existing quartz fiber reinforced wave absorbing composite materials are prone to combust and damage under high-energy laser radiation, and the electromagnetic wave attenuation characteristics of the composite coating are insufficient, making it difficult to meet the comprehensive protection needs of drones and other equipment.
Using the gradient gradient principle, the mixture is brushed layer by layer by layer by surface treatment to form a quartz fiber reinforced composite material that is resistant to high-energy laser radiation and wide frequency absorption. Combined with the hot pressing process, the type of functional filler is optimized. and chemical formula ratio to achieve versatile design of materials.
While maintaining the mechanical strength, it significantly improves the material's high-energy laser radiation resistance and wide-frequency wave absorption performance, meets the different functional needs of structural parts such as drone fuselage and wings, and enhances the equipment's comprehensive protection capabilities.
Smart Images

Figure CN119192627A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wave-absorbing composite materials, and in particular relates to a method for preparing a quartz fiber-reinforced wave-absorbing composite material resistant to high-energy laser irradiation. Background Art
[0002] At present, based on the requirements of lightweight and broadband stealth design, quartz fiber reinforced absorbing composite materials have become one of the main key materials for the load-bearing / secondary load-bearing structural parts of UAV fuselage, wings and other equipment. It has the advantages of good absorbing performance, high strength and low density.
[0003] Generally speaking, ordinary quartz fiber reinforced absorbing composite materials are very prone to burning, damage, and destruction under high-energy laser irradiation. Their extensive use in the load-bearing / secondary load-bearing structures of drone fuselages, wings, and other equipment has greatly limited the survivability of drones and other equipment under high-energy laser irradiation.
[0004] As the power density of high-energy laser irradiation continues to increase, the widespread harm it brings to equipment such as drones is becoming increasingly serious. Quartz fiber reinforced absorbing composite materials can hardly reflect and absorb high-energy lasers. Experiments show that even at tens of W / cm 2 It will also burn through instantly under laser irradiation and has no protection at all.
[0005] In recent years, in order to improve the high-energy laser radiation resistance of quartz fiber reinforced absorbing composite materials, researchers have mostly adopted methods such as plating a metal reflective layer on the surface of quartz fiber reinforced absorbing composite materials or coating the surface with a high-energy laser protective coating. However, there are still problems such as the electromagnetic signal characteristics of equipment such as drones being easily detected by radar, the surface high-energy laser protective coating being easily delaminated and falling off, and the overall weight gain / thickness increasing, which have become key technical difficulties restricting the improvement of the comprehensive protection capabilities of equipment such as drones.
[0006] For example, the invention patent application with patent application number CN111500146A discloses a composite laser ablation-resistant coating, a preparation method and a use method thereof. The composite laser ablation-resistant coating will generate instantaneous high energy under high-energy laser irradiation, thereby causing the zirconium oxide crystal form to change, thereby increasing the reflectivity of the coating surface, and relatively reducing the laser irradiation heat energy, thereby protecting the coating from high-energy laser ablation.
[0007] For example, the invention patent application with patent application number CN113088109A discloses a composite protective coating resistant to high-energy laser ablation and its preparation method. The composite protective coating resistant to high-energy laser ablation has a three-dimensional microporous structure with a pore size of 5-20μm. The coating can effectively resist 7kW / cm 2 (10s) Laser irradiation.
[0008] However, the above inventions only consider the resistance to high-energy laser radiation, but do not consider the electromagnetic wave attenuation characteristics of the composite coating, which makes it difficult to meet the needs of building comprehensive protection capabilities for equipment such as drones.
[0009] For example, the invention patent application with patent application number CN115921254A discloses a wide-band stealth structure, preparation method and application of radar laser on the surface of an aircraft. Its main technical route is to spray a topcoat layer on the absorbing coating, irradiate the topcoat layer with femtosecond laser pulses, and obtain a microstructure on the topcoat layer. Since the topcoat layer itself has a suitable impedance, it does not affect the radar absorbing performance of the absorbing layer. The presence of the microstructure can produce interference with the laser wavelength, absorb the laser, and produce a laser stealth effect, thereby achieving radar-laser stealth. The parameters of the femtosecond laser used are: wavelength 1026nm, power 20W, repetition frequency 2MHz, spot size 2μm, spot moving rate 10mm / s. The processing path is unidirectional.
[0010] For example, the invention patent application with patent application number CN114573037A discloses a method for rapidly preparing absorbing materials by laser irradiation, which uses a simple and easy laser irradiation method to rapidly prepare flexible Fe3O4 / C absorbing materials to achieve broadband absorption in the microwave band. The parameters of the laser used are: wavelength 532nm or 1064nm, power 3-5mW, irradiation time 1-5s.
[0011] For example, the invention patent application with patent application number CN112918025A discloses an ablative anti-insulation and wave-absorbing integrated composite material and its preparation method; it is mainly silicone resin, and a small amount of phenolic resin is added to reduce the residual carbon rate after high-temperature cracking; hollow glass microspheres are used as fillers, which can effectively reduce the material density and thermal conductivity, and can adjust the dielectric constant of the composite material, so that the electrical properties of the material have a larger design space. The laser etching process parameters used are: laser etching power is 5-15W, scanning speed is 200-1000mm / s, and scanning times are 2-10 times.
[0012] However, the above inventions involve the use of laser processing technology to prepare absorbing materials to achieve radar-laser stealth or broadband absorption of microwave electromagnetic waves. The laser power used is generally W-level or mW-level, which is far from the power density level of high-energy laser irradiation.
[0013] At present, in order to achieve a compatible design of high-energy laser resistance, broadband absorption and mechanical strength, researchers mostly use methods such as plating a metal reflective layer on the surface of quartz fiber reinforced absorbing composite materials or coating the surface with a high-energy laser protective coating. Although plating a metal high-reflective layer on the surface of the composite material can significantly improve the ability to withstand high-energy laser irradiation, the underlying quartz fiber reinforced absorbing composite material cannot play a broadband absorbing role, resulting in the overall electromagnetic signal characteristics of the equipment being prominent, which is easily detected by radar reconnaissance, restricting the survivability of equipment such as drones. Although coating the surface of the composite material with a high-energy laser protective coating does not have as great a negative impact on the comprehensive performance of the underlying quartz fiber reinforced absorbing composite material as plating a metal high-reflective layer, there are still problems such as easy delamination and shedding of the coating and significant overall weight gain / thickness. Summary of the invention
[0014] In view of the above technical problems, the present invention provides a method for preparing a quartz fiber reinforced absorbing composite material resistant to high-energy laser irradiation. The preparation method is based on the principle of gradient gradual change, proposes and realizes the coordinated regulation of laser high reflection, high temperature resistance, high heat insulation / ablation resistance and absorbing performance, and takes into account the mechanical properties. By improving the interface characteristics between the resin matrix and the functional filler, a quartz fiber reinforced absorbing composite material resistant to high-energy laser irradiation is developed and cured, thereby realizing the integrated design of high-energy laser irradiation resistance and broadband absorbing structure function.
[0015] In order to solve the above technical problems, the technical solution adopted by the present invention is: A method for preparing a quartz fiber reinforced wave-absorbing composite material resistant to high-energy laser irradiation comprises the following steps: S1. Surface treatment is performed on the inorganic filler, wherein the inorganic filler comprises a filler with a wave absorbing function and a filler with a function of resisting high-energy laser radiation; S2, mixing the resin matrix and the curing agent to obtain a mixture A; S3, mixing the inorganic filler surface-treated in step S1 with the mixture A obtained in step S2 to obtain a mixture B; S4, laying multiple layers of quartz fiber woven fabrics in the mold, and then brushing the mixture B obtained in step S3 layer by layer; compacting and closing the mold, placing it in a hot press for curing, and curing it in an oven to obtain a finished product of a high-energy laser-resistant quartz fiber reinforced absorbing composite material; During the layer-by-layer brushing: from bottom to top, the mass fraction of each layer of quartz fiber woven fabric is controlled to be 30 to 70 parts, and the mass fraction of each layer of brushed mixture B is controlled to be 30 to 70 parts respectively; From bottom to top, the mass fraction of each layer of quartz fiber woven fabric gradually decreases; the mass fraction of the wave-absorbing functional filler in the mixture B gradually decreases; and the mass fraction of the high-energy laser irradiation-resistant functional filler gradually increases.
[0016] Preferably, in step S1, the high-energy laser irradiation resistant functional filler is any one or more of silicon carbide whiskers, zirconium oxide, aluminum oxide and silicon dioxide; the wave absorbing functional filler is manganese zinc ferrite or strontium barium ferrite; The surface treatment of the inorganic filler refers to: immersing the inorganic filler in a solution of silane coupling agent and ethanol diluted in a mass ratio of 3 to 5:100, the immersion time is 0.5 to 2 hours, the treatment temperature is room temperature, and drying at 50 to 60° C. after treatment.
[0017] Preferably, in the step S2, the resin matrix and the curing agent are mixed in a mass ratio of 100:0.5-2.0 to obtain a mixture A; in the step S3, the resin matrix and the inorganic filler are mixed in a mass ratio of 100:30-45 to obtain a mixture B.
[0018] Preferably, the resin matrix is any one or more of silicone resin, phenolic resin, and epoxy resin; the curing agent is any one or more of vinyltrimethoxysilane, benzenesulfonic acid, and benzoyl peroxide.
[0019] Preferably, the quartz fiber woven fabric in S4 is woven from surface-treated quartz fibers, and is obtained by soaking in a solution consisting of a silane coupling agent and ethanol and drying; the width of the quartz fiber woven fabric is 300-1000 mm, and the mesh area is 0.5-3.0 mm 2 .
[0020] Preferably, in S4, compact and close the mold, heat the hot press to 120-125°C, place the mold on the hot press, pressurize to 20-25MPa, and maintain the curing time for 1.5-2h; after the curing is completed, cool to room temperature, release the pressure, take out the cured high-energy laser irradiation resistant quartz fiber reinforced absorbing composite material from the mold, place it in an oven for post-curing, the post-curing temperature is 120-150°C, the post-curing time is 24-48h, and a finished high-energy laser irradiation resistant quartz fiber reinforced absorbing composite material is obtained.
[0021] Preferably, the quartz fiber is surface treated with distilled water, acetone and HNO3 solution; the silane coupling agent and ethanol are diluted in a mass ratio of 3 to 5:100, the immersion time is 0.5 to 2 hours, the treatment temperature is room temperature, and the treatment is dried at 50 to 60°C.
[0022] Preferably, surface treatment of the quartz fiber with distilled water, acetone and HNO3 solution means: first cleaning the surface of the quartz fiber with distilled water, soaking it in acetone for 0.5 to 5 hours to remove the sizing agent, and then cleaning it with distilled water, soaking the cleaned quartz fiber in an HNO3 solution with a concentration of 50 to 70% and a temperature of 70 to 100°C for 1 to 8 hours, and then cleaning it with distilled water.
[0023] Preferably, the silane coupling agent is any one or more of γ-aminopropyltriethoxysilane (KH550), γ-glycidyloxypropyltrimethoxysilane (KH560), and γ-methacryloxypropyltrimethoxysilane (KH570).
[0024] Preferably, the quartz fiber is any one or more of quartz fibers with a single fiber diameter of 5 μm, 7.5 μm, 9 μm, 10.5 μm, and 11 μm; the quartz fiber woven fabric is any one or more of a two-dimensional two-dimensional woven fabric, a two-dimensional three-dimensional woven fabric, or a two-dimensional four-directional woven fabric.
[0025] Compared with the prior art, the present invention has the following beneficial effects: The technical solution proposed by the present invention is to add the surface-treated high-energy laser irradiation resistant filler and the broadband absorbing filler into the quartz fiber reinforced composite material system according to the chemical formula ratio to prepare the high-energy laser irradiation resistant quartz fiber reinforced absorbing composite material.
[0026] The present invention proposes and optimizes the types, chemical formulas and compounding ratios of high-energy laser irradiation resistant fillers and broadband wave-absorbing fillers based on the principle of gradient gradual design, taking into full consideration the thermal ablation and thermal decomposition processes of materials under high-energy laser irradiation. The optimized composite material system can meet the different functional / performance design requirements of the load-bearing / secondary load-bearing structural parts of the fuselage, wings and other equipment of drones, and realizes the compatible design of high-energy laser resistance, broadband wave absorption and mechanical strength.
[0027] In the specific implementation process, the surface treatment with coupling agent makes the dispersion of various functional fillers in the resin matrix more uniform and stable, and the interface bonding force is stronger; the hot pressing molding process is used for one-time molding, which simplifies the preparation process and is beneficial to improving the mechanical strength of the composite material.
[0028] Compared with traditional quartz fiber reinforced absorbing composite materials, the present invention proposes to use silicon carbide whiskers, zirconium oxide, aluminum oxide, silicon dioxide, manganese zinc ferrite, strontium barium ferrite and other inorganic fillers as the main high-energy laser irradiation resistant and broadband absorbing fillers, which can maintain the original physical and mechanical properties while having the advantages of low density, easy molding, strong high-energy laser irradiation resistance, wide absorbing frequency band, etc.
[0029] In the preparation method, quartz fiber and inorganic fillers such as silicon carbide whiskers, zirconium oxide, alumina, silicon dioxide, manganese zinc ferrite, and strontium barium ferrite are first surface treated with an ethanol solution of a silane coupling agent, and then mixed with silicone resin, phenolic resin or epoxy resin, so that the various functional fillers are dispersed more evenly and stably in the resin matrix and the interface bonding force is stronger, which is beneficial to improve the mechanical strength of the composite material.
[0030] Under the premise of fully considering the thermal ablation and thermal decomposition process of materials under high-energy laser irradiation, based on the impedance matching design principle, the types, chemical formulas and compound ratio ranges of high-energy laser irradiation resistant fillers and broadband absorbing fillers are proposed and optimized. The optimized composite material system can meet the different functional / performance design requirements of the load-bearing / secondary load-bearing structural parts of the fuselage, wings and other equipment of drones, and realize the compatible design of high-energy laser resistance, broadband absorbing and mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a preparation flow chart of the present invention; Figure 2 This is a reflectivity test curve of the quartz fiber reinforced wave-absorbing composite material resistant to high-energy laser irradiation before and after irradiation according to Example 2 of the present invention. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments.
[0033] Embodiment 1: A preparation method of a quartz fiber reinforced wave absorbing composite material resistant to high energy laser irradiation comprises the following steps: S1. Dilute the coupling agent KH550 and ethanol in a mass ratio of 3:100, and soak silicon carbide whiskers, zirconium oxide, aluminum oxide, and manganese-zinc ferrite in the above solution for 0.5 h at room temperature, and dry at 50° C. after treatment to obtain an inorganic filler.
[0034] S2. Mixing a silicone resin matrix and vinyl trimethylsiloxane in a mass ratio of 100:0.5 to obtain a mixture A.
[0035] S3, immersing the inorganic filler obtained in step S1 into the mixture A prepared in step S2, and mixing the silicone resin matrix and the inorganic filler in a mass ratio of 100:45 to obtain a mixture B.
[0036] S4. According to the impedance matching design requirements, four layers of quartz fiber woven fabric are laid in the mold coated with the release agent, and then the mixture B is brushed layer by layer; the specific operation is: laying one layer, brushing one layer, laying another layer, brushing another layer, and so on; From bottom to top, the weight of each layer of quartz fiber woven fabric is controlled to be 60 parts, 50 parts, 40 parts and 30 parts respectively, and the weight of each layer of brush-coated mixture B is controlled to be 40 parts, 50 parts, 60 parts and 30 parts respectively, and then the mold is compacted and closed; Heat the hot press to 120°C, place the mold on the hot press, pressurize to 20MPa, and maintain the curing time for 2h; After the curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser resistant quartz fiber reinforced absorbing composite material is taken out of the mold and placed in an oven for post-curing. The post-curing temperature is 120°C and the post-curing time is 48 hours to obtain a finished high-energy laser resistant quartz fiber reinforced absorbing composite material.
[0037] The quartz fiber woven fabric in the above step S4 is obtained by the following preparation method: (1) After cleaning the surface of a quartz fiber with a single-filament diameter of 5 μm with distilled water, soak it in acetone for 0.5 h to remove the sizing agent, and then wash it with distilled water; soak the cleaned quartz fiber in a 50% HNO3 solution at 100°C for 8 h, and then wash it with distilled water.
[0038] (2) The quartz fiber is woven into a two-dimensional bidirectional woven fabric with a width of 600 mm and a mesh area of 0.5 mm. 2 , cut into 300mm×300mm as required; (3) Dilute the coupling agent KH550 and ethanol in a mass ratio of 3:100, and soak the quartz fiber woven fabric in the above solution for 0.5 h at room temperature and dry at 50°C after treatment.
[0039] Embodiment 2: A preparation method of a quartz fiber reinforced wave absorbing composite material resistant to high energy laser irradiation comprises the following steps: S1. Dilute the coupling agent KH560 and ethanol in a mass ratio of 4:100, and soak silicon carbide whiskers, zirconium oxide, aluminum oxide, and strontium barium ferrite in the above solution for 1 hour at room temperature, and dry at 50°C after treatment to obtain an inorganic filler.
[0040] S2. Mixing a phenolic resin matrix and benzenesulfonic acid in a mass ratio of 100:0.5 to obtain a mixture A.
[0041] S3, immersing the inorganic filler obtained in step S1 into the mixture A prefabricated in step S2, and mixing the phenolic resin matrix and the inorganic filler in a mass ratio of 100:45 to obtain a mixture B.
[0042] S4. According to the impedance matching design requirements, four layers of quartz fiber woven fabric are laid in the mold coated with the release agent, and then the mixture B is brushed layer by layer; the specific operation is: laying one layer, brushing one layer, laying another layer, brushing another layer, and so on; From bottom to top, the weight of each layer of quartz fiber woven fabric is controlled to be 60 parts, 50 parts, 40 parts and 30 parts respectively, and the weight of each layer of brush-coated mixture B is controlled to be 40 parts, 50 parts, 60 parts and 30 parts respectively, and then the mold is compacted and closed; Heat the hot press to 125°C, place the mold on the hot press, pressurize to 25MPa, and maintain the curing time for 1.5h; After the curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser resistant quartz fiber reinforced absorbing composite material is taken out of the mold and placed in an oven for post-curing at a post-curing temperature of 150°C and a post-curing time of 24 hours to obtain a finished high-energy laser resistant quartz fiber reinforced absorbing composite material.
[0043] The quartz fiber woven fabric in the above step S4 is obtained by the following preparation method: (1) After cleaning the surface of a quartz fiber with a single filament diameter of 7.5 μm with distilled water, soak it in acetone for 1 h to remove the sizing agent, and then wash it with distilled water; soak the cleaned 3K quartz fiber in a HNO3 solution with a concentration of 60% and a temperature of 90°C for 6 h, and then wash it with distilled water.
[0044] (2) The quartz fiber is woven into a two-dimensional three-dimensional woven fabric with a loom, with a width of 600 mm and a mesh area of 0.75 mm 2 , cut into 600mm×600mm as required; (3) Dilute the coupling agent KH560 and ethanol in a mass ratio of 4:100, and soak the quartz fiber woven fabric in the above solution for 1 hour at room temperature, and dry it at 50°C after treatment.
[0045] Embodiment three: A preparation method of a quartz fiber reinforced wave absorbing composite material resistant to high energy laser irradiation comprises the following steps: S1. Dilute the coupling agent KH570 and ethanol in a mass ratio of 5:100, and soak silicon carbide whiskers, aluminum oxide, and strontium barium ferrite in the above solution for 1.5 hours at room temperature. After treatment, dry at 60°C to obtain an inorganic filler.
[0046] S2. Mixture A obtained by mixing the epoxy resin matrix and benzoyl peroxide in a mass ratio of 100:1.
[0047] S3, immersing the inorganic filler obtained in step S1 into the mixture A prefabricated in step S2, and mixing the epoxy resin matrix and the inorganic filler in a mass ratio of 100:45 to obtain a mixture B.
[0048] S4. According to the impedance matching design requirements, four layers of quartz fiber woven fabric are laid in the mold coated with the release agent, and then the mixture B is brushed layer by layer; the specific operation is: laying one layer, brushing one layer, laying another layer, brushing another layer, and so on; From bottom to top, the weight of each layer of quartz fiber woven fabric is controlled to be 60 parts, 50 parts, 40 parts and 30 parts respectively, and the weight of each layer of brush-coated mixture B is controlled to be 40 parts, 50 parts, 60 parts and 30 parts respectively, and then the mold is compacted and closed; Heat the hot press to 120°C, place the mold on the hot press, pressurize to 20MPa, and maintain the curing time for 2h; After the curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser resistant quartz fiber reinforced absorbing composite material is taken out of the mold and placed in an oven for post-curing at a post-curing temperature of 125°C and a post-curing time of 48 hours to obtain a finished high-energy laser resistant quartz fiber reinforced absorbing composite material.
[0049] The quartz fiber woven fabric in the above step S4 is obtained by the following preparation method: (1) After cleaning the surface of a quartz fiber with a single filament diameter of 9 μm with distilled water, soak it in acetone for 2 h to remove the sizing agent, and then wash it with distilled water; soak the cleaned quartz fiber in a HNO3 solution with a concentration of 70% and a temperature of 80°C for 4 h, and then wash it with distilled water.
[0050] (2) The quartz fiber is woven into a two-dimensional four-way woven fabric with a loom, with a width of 1000 mm and a mesh area of 1.5 mm 2 , cut into 1000mm×1000mm as required; (3) Dilute the coupling agent KH570 and ethanol in a mass ratio of 5:100, and soak the quartz fiber woven fabric in the above solution for 1.5 hours at room temperature, and dry at 60°C after treatment.
[0051] Embodiment 4: A preparation method of a quartz fiber reinforced wave absorbing composite material resistant to high energy laser irradiation comprises the following steps: S1. Dilute the coupling agent KH560 and ethanol in a mass ratio of 4:100, and soak silicon carbide whiskers, zirconium oxide, silicon dioxide, manganese zinc ferrite, and strontium barium ferrite in the above solution for 2 hours at room temperature, and dry at 60°C after treatment to obtain an inorganic filler.
[0052] S2. Mixing a phenolic resin matrix and benzenesulfonic acid in a mass ratio of 100:1.5 to obtain a mixture A.
[0053] S3, immersing the inorganic filler obtained in step S1 into the mixture A prefabricated in step S2, and mixing the phenolic resin matrix and the inorganic filler in a mass ratio of 100:40 to obtain a mixture B.
[0054] S4. According to the impedance matching design requirements, three layers of quartz fiber woven fabric are laid in the mold coated with the release agent, and then the mixture B is brushed layer by layer; the specific operation is: laying one layer, brushing one layer, laying another layer, brushing another layer, and so on; From bottom to top, the weight of each layer of quartz fiber woven fabric is controlled to be 60 parts, 50 parts and 40 parts respectively, and the weight of each layer of brush-coated mixture B is controlled to be 40 parts, 50 parts and 60 parts respectively, and then the mold is compacted and closed; Heat the hot press to 125°C, place the mold on the hot press, pressurize to 25MPa, and maintain the curing time for 1.5h; After the curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser resistant quartz fiber reinforced absorbing composite material is taken out of the mold and placed in an oven for post-curing at a post-curing temperature of 150°C and a post-curing time of 24 hours to obtain a finished high-energy laser resistant quartz fiber reinforced absorbing composite material.
[0055] The quartz fiber woven fabric in the above step S4 is obtained by the following preparation method: (1) After cleaning the surface of a quartz fiber with a single-filament diameter of 10.5 μm with distilled water, soak it in acetone for 3 h to remove the sizing agent, and then wash it with distilled water; soak the cleaned quartz fiber in a HNO3 solution with a concentration of 70% and a temperature of 100°C for 8 h, and then wash it with distilled water.
[0056] (2) The quartz fiber is woven into a two-dimensional three-dimensional woven fabric with a loom, with a width of 1000 mm and a mesh area of 2.0 mm 2 , cut into 1000mm×1000mm as required; (3) Dilute the coupling agent KH560 and ethanol in a mass ratio of 4:100, and soak the quartz fiber woven fabric in the above solution for 2 hours at room temperature, and dry it at 60°C after treatment.
[0057] Embodiment five: A preparation method of a quartz fiber reinforced wave absorbing composite material resistant to high energy laser irradiation comprises the following steps: S1. Dilute the coupling agent KH570 and ethanol in a mass ratio of 5:100, and soak silicon carbide whiskers, silicon dioxide, manganese zinc ferrite, and strontium barium ferrite in the above solution for 2 hours at room temperature. After treatment, dry at 60°C to obtain an inorganic filler.
[0058] S2. Mixing a phenolic resin matrix and benzenesulfonic acid in a mass ratio of 100:2 to obtain a mixture A.
[0059] S3, immersing the inorganic filler obtained in step S1 into the mixture A prepared in step S2, and mixing the silicone resin matrix and the inorganic filler in a mass ratio of 100:40 to obtain a mixture B.
[0060] S4. According to the impedance matching design requirements, three layers of quartz fiber woven fabric are laid in the mold coated with the release agent, and then the mixture B is brushed layer by layer; the specific operation is: laying one layer, brushing one layer, laying another layer, brushing another layer, and so on; From bottom to top, the weight of each layer of quartz fiber woven fabric is controlled to be 60 parts, 50 parts and 40 parts respectively, and the weight of each layer of brush-coated mixture B is controlled to be 40 parts, 50 parts and 60 parts respectively, and then the mold is compacted and closed; Heat the hot press to 120°C, place the mold on the hot press, pressurize to 20MPa, and maintain the curing time for 2h; After the curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser resistant quartz fiber reinforced absorbing composite material is taken out of the mold and placed in an oven for post-curing. The post-curing temperature is 120°C and the post-curing time is 48 hours to obtain a finished high-energy laser resistant quartz fiber reinforced absorbing composite material.
[0061] The quartz fiber woven fabric in the above step S4 is obtained by the following preparation method: (1) After cleaning the surface of a quartz fiber with a single-filament diameter of 11 μm with distilled water, soak it in acetone for 4 h to remove the sizing agent, and then wash it with distilled water; soak the cleaned quartz fiber in a 50% HNO3 solution at 100°C for 6 h, and then wash it with distilled water.
[0062] (2) The quartz fiber is woven into a two-dimensional three-dimensional woven fabric with a width of 1000 mm and a mesh area of 2.5 mm. 2 , cut into 1000mm×1000mm as required; (3) Dilute the coupling agent KH570 and ethanol in a mass ratio of 5:100, and soak the quartz fiber woven fabric in the above solution for 2 hours at room temperature, and dry it at 60°C after treatment.
[0063] Embodiment six: A preparation method of a quartz fiber reinforced wave absorbing composite material resistant to high energy laser irradiation comprises the following steps: S1. Dilute the coupling agent KH550 and ethanol in a mass ratio of 4:100, and soak silicon carbide whiskers, zirconium oxide, silicon dioxide, manganese zinc ferrite, and strontium barium ferrite in the above solution for 1.5 hours at room temperature, and dry at 60°C after treatment to obtain an inorganic filler.
[0064] S2. Mixture A obtained by mixing the epoxy resin matrix and benzoyl peroxide in a mass ratio of 100:1.
[0065] S3, immersing the inorganic filler obtained in step S1 into the mixture A prefabricated in step S2, and mixing the epoxy resin matrix and the inorganic filler in a mass ratio of 100:30 to obtain a mixture B.
[0066] S4. According to the impedance matching design requirements, three layers of quartz fiber woven fabric are laid in the mold coated with the release agent, and then the mixture B is brushed layer by layer; the specific operation is: laying one layer, brushing one layer, laying another layer, brushing another layer, and so on; From bottom to top, the weight of each layer of quartz fiber woven fabric is controlled to be 50 parts, 40 parts and 30 parts respectively, and the weight of each layer of brush-coated mixture B is controlled to be 50 parts, 60 parts and 70 parts respectively, and then the mold is compacted and closed; Heat the hot press to 120°C, place the mold on the hot press, pressurize to 20MPa, and maintain the curing time for 2h; After the curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser resistant quartz fiber reinforced absorbing composite material is taken out of the mold and placed in an oven for post-curing at a post-curing temperature of 125°C and a post-curing time of 48 hours to obtain a finished high-energy laser resistant quartz fiber reinforced absorbing composite material.
[0067] The quartz fiber woven fabric in the above step S4 is obtained by the following preparation method: (1) After cleaning the surface of a quartz fiber with a single fiber diameter of 5 μm with distilled water, soak it in acetone for 5 h to remove the sizing agent, and then wash it with distilled water; soak the cleaned quartz fiber in a 50% HNO3 solution at 70°C for 8 h, and then wash it with distilled water.
[0068] (2) The quartz fiber is woven into a two-dimensional four-way woven fabric with a loom, with a width of 1000 mm and a mesh area of 3.0 mm 2 , cut into 1000mm×1000mm as required; (3) Dilute the coupling agent KH550 and ethanol in a mass ratio of 4:100, and soak the quartz fiber woven fabric in the above solution for 1.5 hours at room temperature, and dry at 60°C after treatment.
[0069] Embodiment seven: A preparation method of a quartz fiber reinforced wave absorbing composite material resistant to high energy laser irradiation comprises the following steps: S1. Dilute the coupling agent KH550 and ethanol in a mass ratio of 5:100, and soak silicon carbide whiskers, aluminum oxide, manganese zinc ferrite, and strontium barium ferrite in the above solution for 2 hours at room temperature. After treatment, dry at 60°C to obtain an inorganic filler.
[0070] S2. Mixture A obtained by mixing a silicone resin matrix and vinyl trimethylsiloxane in a mass ratio of 100:2.
[0071] S3, immersing the inorganic filler obtained in step S1 into the mixture A prepared in step S2, and mixing the silicone resin matrix and the inorganic filler in a mass ratio of 100:35 to obtain a mixture B.
[0072] S4. According to the impedance matching design requirements, in the mold coated with the release agent, 1 layer of quartz fiber woven fabric with a single wire diameter of 9 μm, 1 layer of quartz fiber woven fabric with a single wire diameter of 7.5 μm, 1 layer of quartz fiber woven fabric with a single wire diameter of 9 μm, 1 layer of quartz fiber woven fabric with a single wire diameter of 7.5 μm, and 1 layer of quartz fiber woven fabric with a single wire diameter of 9 μm are laid from bottom to top, and then the mixture B is brushed layer by layer; the specific operation is: laying one layer, brushing one layer, laying another layer, brushing another layer, and so on; From bottom to top, the weight of each layer of quartz fiber woven fabric is controlled to be 70 parts, 60 parts, 50 parts, 40 parts and 30 parts respectively, and the weight of each layer of brush-coated mixture B is controlled to be 30 parts, 40 parts, 50 parts, 60 parts and 70 parts respectively, and the mold is compacted and closed; Heat the hot press to 150°C, place the mold on the hot press, pressurize to 25MPa, and maintain the curing time for 1.5h; After the curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser resistant quartz fiber reinforced absorbing composite material is taken out of the mold and placed in an oven for post-curing at a post-curing temperature of 125°C and a post-curing time of 48 hours to obtain a finished high-energy laser resistant quartz fiber reinforced absorbing composite material.
[0073] The quartz fiber woven fabric in the above step S4 is obtained by the following preparation method: (1) After cleaning the surfaces of quartz fibers with a single filament diameter of 7.5 μm and quartz fibers with a single filament diameter of 9 μm with distilled water, they were immersed in acetone for 4.5 h to remove the sizing agent and then washed with distilled water. The two types of washed quartz fibers were immersed in a 50% HNO3 solution at a temperature of 100 °C for 5 h and then washed with distilled water.
[0074] (2) The two diameters of quartz fibers were woven into two-dimensional bidirectional fabrics using a loom. The width was 600 mm and the mesh area was 0.5 mm. 2 , 1.0mm 2, cut into 600mm×600mm as required; (3) The coupling agent KH550 and ethanol were diluted in a mass ratio of 5:100, and the quartz fiber woven fabrics of two diameters were immersed in the above solution for 2 hours at room temperature and dried at 60°C after treatment.
[0075] Embodiment eight: A preparation method of a quartz fiber reinforced wave absorbing composite material resistant to high energy laser irradiation comprises the following steps: S1. Dilute the coupling agent KH570 and ethanol in a mass ratio of 3.5:100, and soak silicon carbide whiskers, aluminum oxide, manganese zinc ferrite, and strontium barium ferrite in the above solution for 0.5 h at room temperature, and dry at 60° C. after treatment to obtain an inorganic filler.
[0076] S2. Mixing a phenolic resin matrix and benzenesulfonic acid in a mass ratio of 100:2 to obtain a mixture A.
[0077] S3, immersing the inorganic filler obtained in step S1 into the mixture A prefabricated in step S2, and mixing the phenolic resin matrix and the inorganic filler in a mass ratio of 100:40 to obtain a mixture B.
[0078] S4. According to the impedance matching design requirements, in the mold coated with the release agent, 1 layer of quartz fiber woven fabric with a single wire diameter of 11 μm, 1 layer of quartz fiber woven fabric with a single wire diameter of 10.5 μm, 1 layer of quartz fiber woven fabric with a single wire diameter of 11 μm, 1 layer of quartz fiber woven fabric with a single wire diameter of 10.5 μm, and 1 layer of quartz fiber woven fabric with a single wire diameter of 11 μm are laid from bottom to top, and then the mixture B is brushed layer by layer; the specific operation is: laying one layer, brushing one layer, laying another layer, brushing another layer, and so on; From bottom to top, the weight of each layer of quartz fiber woven fabric is controlled to be 70 parts, 60 parts, 50 parts, 40 parts and 30 parts respectively, and the weight of each layer of brush-coated mixture B is controlled to be 30 parts, 40 parts, 50 parts, 60 parts and 70 parts respectively, and the mold is compacted and closed; Heat the hot press to 125°C, place the mold on the hot press, pressurize to 25MPa, and maintain the curing time for 1.5h; After the curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser resistant quartz fiber reinforced absorbing composite material is taken out of the mold and placed in an oven for post-curing at a post-curing temperature of 150°C and a post-curing time of 24 hours to obtain a finished high-energy laser resistant quartz fiber reinforced absorbing composite material.
[0079] The quartz fiber woven fabric in the above step S4 is obtained by the following preparation method: (1) After cleaning the surfaces of quartz fibers with a single filament diameter of 10.5 μm and quartz fibers with a single filament diameter of 11 μm with distilled water, they were immersed in acetone for 5 h to remove the sizing agent and then washed with distilled water. The two types of washed quartz fibers were immersed in a HNO3 solution with a concentration of 65% and a temperature of 100 °C for 3 h and then washed with distilled water.
[0080] (2) The two diameters of quartz fibers were woven into two-dimensional three-dimensional woven fabrics using a loom. The width was 1000 mm and the mesh area was 1.5 mm. 2 , 2.0mm 2 , cut into 1000mm×1000mm as required; (3) The coupling agent KH570 and ethanol were diluted in a mass ratio of 3.5:100, and the quartz fiber woven fabrics of two diameters were immersed in the above solution for 0.5 h, the treatment temperature was room temperature, and the treatment was dried at 60 °C.
[0081] Embodiment nine: A preparation method of a quartz fiber reinforced wave absorbing composite material resistant to high energy laser irradiation comprises the following steps: S1. Dilute the coupling agent KH570 and ethanol in a mass ratio of 5:100, and soak alumina and strontium barium ferrite in the above solution for 1 hour at room temperature, and dry at 60°C after treatment to obtain an inorganic filler.
[0082] S2. Mixing a phenolic resin matrix and benzenesulfonic acid in a mass ratio of 100:1.5 to obtain a mixture A.
[0083] S3, immersing the inorganic filler obtained in step S1 into the mixture A prefabricated in step S2, and mixing the phenolic resin matrix and the inorganic filler in a mass ratio of 100:45 to obtain a mixture B.
[0084] S4. According to the impedance matching design requirements, in the mold coated with the release agent, 1 layer of quartz fiber woven fabric with a single wire diameter of 5 μm, 1 layer of quartz fiber woven fabric with a single wire diameter of 7.5 μm, 1 layer of quartz fiber woven fabric with a single wire diameter of 5 μm, 1 layer of quartz fiber woven fabric with a single wire diameter of 7.5 μm, and 1 layer of quartz fiber woven fabric with a single wire diameter of 5 μm are laid from bottom to top, and then the mixture B is brushed layer by layer; the specific operation is: laying one layer, brushing one layer, laying another layer, brushing another layer, and so on; From bottom to top, the weight of each layer of quartz fiber woven fabric is controlled to be 70 parts, 60 parts, 50 parts, 40 parts and 30 parts respectively, and the weight of each layer of brush-coated mixture B is controlled to be 30 parts, 40 parts, 50 parts, 60 parts and 70 parts respectively, and the mold is compacted and closed; Heat the hot press to 125°C, place the mold on the hot press, pressurize to 25MPa, and maintain the curing time for 1.5h; After the curing is completed, the temperature is lowered to room temperature and the pressure is released. The cured high-energy laser resistant quartz fiber reinforced absorbing composite material is taken out of the mold and placed in an oven for post-curing at a post-curing temperature of 150°C and a post-curing time of 24 hours to obtain a finished high-energy laser resistant quartz fiber reinforced absorbing composite material.
[0085] The quartz fiber woven fabric in the above step S4 is obtained by the following preparation method: (1) After cleaning the surfaces of quartz fibers with a single filament diameter of 5 μm and quartz fibers with a single filament diameter of 7.5 μm with distilled water, they were immersed in acetone for 5 h to remove the sizing agent and then washed with distilled water. The two types of washed quartz fibers were immersed in a HNO3 solution with a concentration of 65% and a temperature of 100 °C for 3 h and then washed with distilled water.
[0086] (2) The two diameters of quartz fibers were woven into two-dimensional three-dimensional woven fabrics using a loom. The width was 1000 mm and the mesh area was 1.5 mm. 2 , 2.0mm 2 , cut into 1000mm×1000mm as required; (3) The coupling agent KH570 and ethanol were diluted in a mass ratio of 5:100, and the quartz fiber woven fabrics of two diameters were immersed in the above solution for 5 hours at room temperature and dried at 60°C after treatment.
[0087] Only the preferred embodiments of the present invention have been described in detail above, but the present invention is not limited to the above embodiments.
Claims
1. A method for preparing a quartz fiber reinforced wave absorbing composite material resistant to high energy laser irradiation, characterized in that: The following steps are involved: S1. Surface treatment is performed on the inorganic filler, wherein the inorganic filler comprises a filler with a wave absorbing function and a filler with a function of resisting high-energy laser radiation; S2, mixing the resin matrix and the curing agent to obtain a mixture A; S3, mixing the inorganic filler surface-treated in step S1 with the mixture A obtained in step S2 to obtain a mixture B; S4, laying multiple layers of quartz fiber woven fabrics in the mold, and then brushing the mixture B obtained in step S3 layer by layer; compacting and closing the mold, placing it in a hot press for curing, and curing it in an oven to obtain a finished product of a high-energy laser-resistant quartz fiber reinforced absorbing composite material; During the layer-by-layer brushing: from bottom to top, the mass fraction of each layer of quartz fiber woven fabric is controlled to be 30 to 70 parts, and the mass fraction of each layer of brushed mixture B is controlled to be 30 to 70 parts respectively; From bottom to top, the mass fraction of each layer of quartz fiber woven fabric gradually decreases; the mass fraction of the wave-absorbing functional filler in the mixture B gradually decreases; and the mass fraction of the high-energy laser irradiation-resistant functional filler gradually increases.
2. The method for preparing the quartz fiber reinforced wave absorbing composite material resistant to high energy laser irradiation according to claim 1, characterized in that: In the step S1, the high-energy laser irradiation resistant functional filler is any one or more of silicon carbide whiskers, zirconium oxide, aluminum oxide and silicon dioxide; the wave absorbing functional filler is manganese zinc ferrite or strontium barium ferrite; The surface treatment of the inorganic filler refers to: immersing the inorganic filler in a solution of silane coupling agent and ethanol diluted in a mass ratio of 3 to 5:100, the immersion time is 0.5 to 2 hours, the treatment temperature is room temperature, and drying at 50 to 60° C. after treatment.
3. The method for preparing the high-energy laser irradiation-resistant quartz fiber reinforced microwave-absorbing composite material according to claim 1, characterized in that: In the step S2, the resin matrix and the curing agent are mixed in a mass ratio of 100:0.5-2.0 to obtain a mixture A; in the step S3, the resin matrix and the inorganic filler are mixed in a mass ratio of 100:30-45 to obtain a mixture B.
4. The method for preparing the quartz fiber reinforced wave absorbing composite material resistant to high energy laser irradiation according to claim 1 or 3, characterized in that: The resin matrix is any one or more of silicone resin, phenolic resin and epoxy resin; the curing agent is any one or more of vinyl trimethoxy silane, benzene sulfonic acid and benzoyl peroxide.
5. The method for preparing the high-energy laser irradiation-resistant quartz fiber reinforced microwave-absorbing composite material according to claim 1, characterized in that: The quartz fiber woven fabric in S4 is woven from surface-treated quartz fibers, and is obtained by soaking and drying a solution composed of a silane coupling agent and ethanol; the width of the quartz fiber woven fabric is 300-1000 mm, and the mesh area is 0.5-3.0 mm 2 .
6. The method for preparing the quartz fiber reinforced wave absorbing composite material resistant to high energy laser irradiation according to claim 1 or 5, characterized in that: In the S4, the mold is compacted and closed, the temperature of the hot press is increased to 120-125° C., the mold is placed on the hot press, the pressure is increased to 20-25 MPa, and the curing time is maintained for 1.5-2 hours; after the curing is completed, the temperature is lowered to room temperature and the pressure is released, and the cured quartz fiber reinforced absorbing composite material resistant to high-energy laser radiation is taken out of the mold and placed in an oven for post-curing at a post-curing temperature of 120-150° C. and a post-curing time of 24-48 hours to obtain a finished product of the quartz fiber reinforced absorbing composite material resistant to high-energy laser radiation.
7. The method for preparing the high-energy laser irradiation-resistant quartz fiber reinforced microwave-absorbing composite material according to claim 5, characterized in that: The quartz fiber is surface treated with distilled water, acetone and HNO3 solution; the silane coupling agent and ethanol are diluted in a mass ratio of 3 to 5:100, the immersion time is 0.5 to 2 hours, the treatment temperature is room temperature, and the treatment is dried at 50 to 60°C.
8. The method for preparing the quartz fiber reinforced wave absorbing composite material resistant to high energy laser irradiation according to claim 7, characterized in that: The surface treatment of quartz fiber with distilled water, acetone and HNO3 solution means: first, the surface of the quartz fiber is cleaned with distilled water, then immersed in acetone for 0.5 to 5 hours to remove the sizing agent, and then washed with distilled water, and the cleaned quartz fiber is immersed in an HNO3 solution with a concentration of 50 to 70% and a temperature of 70 to 100° C. for 1 to 8 hours, and then washed with distilled water.
9. The method for preparing the quartz fiber reinforced wave absorbing composite material resistant to high energy laser irradiation according to claim 2 or 5, characterized in that: The silane coupling agent is any one or more of γ-aminopropyltriethoxysilane (KH550), γ-glycidyloxypropyltrimethoxysilane (KH560), and γ-methacryloxypropyltrimethoxysilane (KH570).
10. The method for preparing the quartz fiber reinforced wave absorbing composite material resistant to high energy laser irradiation according to claim 5, characterized in that: The quartz fiber is any one or more of quartz fibers with a single fiber diameter of 5 μm, 7.5 μm, 9 μm, 10.5 μm, and 11 μm; the quartz fiber woven fabric is any one or more of two-dimensional two-dimensional woven fabric, two-dimensional three-dimensional woven fabric, or two-dimensional four-dimensional woven fabric.
Citation Information
Patent Citations
Composite laser-ablation-resistant paint, and preparation method and use method thereof
CN111500146A
Ablation type heat insulation and wave absorption integrated composite material and preparation method thereof
CN112918025A
Composite protective coating resistant to high-energy laser ablation and preparation method thereof
CN113088109A
Method for rapidly preparing wave-absorbing material through laser irradiation
CN114573037A
Aircraft surface radar laser broadband stealth structure, preparation method and application
CN115921254A
